Environmental Sanitation Planning: Feasibility of the CLUES Framework in a Malawian Small Town - Mtika, Wema Meranda; Tilley, Elizabeth (Frontiers in Environmental Science, 2020)
Compared to the growing mega-cities or the languishing rural areas, small towns are generally less prioritized by governments and donors, both because they appear less immediately troublesome and because they defy easy classification. However, small towns bear the problems of both density extremes: on one hand, small towns face rapid population growth and struggle to collect revenue from the growing tax base, but on the other hand, do not have the political might or institutional capacity to lobby for services and resources from central government and as a result, must find ways of providing big-city services, with rural-area means. The Community-Led Urban Environmental Sanitation (CLUES) tool was developed to assist small towns with the planning and implementation of environmental sanitation infrastructure and services; through a participatory, action-research project, this work tested the financial, social, and technical feasibility of following the CLUES framework in Luchenza, a Malawian small town. Results obtained over the 2 year, 7-step process revealed that the high turnover of government staff affected institutional knowledge retention, acceptance and continuity and ultimately the potential to engage in a successful planning exercise. Because baseline data was outdated or non-existent, data collection activities consumed unexpected amounts of time, and the results were, because of internal movement and politics, difficult to disseminate and leverage. Most importantly, stakeholder participation was limited and relied on participation and transportation payments, which have become a permanent feature of “community development” in Malawi. Following the CLUES process was expensive, time consuming and politically fraught; it is unlikely that any small town in Malawi would be able to follow the process as outlined. A simplified version, making use of available data and followed only by small towns with a functioning planning department, adequate tax collection, organized community groups and a budget for final implementation would have a greater potential to succeed.